Molecular Insights Into Therapeutic Potential of Autophagy Modulation by Natural Products for Cancer Stem Cells - Rahman, Md. Ataur; Saha, Subbroto Kumar; Rahman, Md Saidur; Uddin, Md Jamal; Uddin, Md. Sahab; Pang, Myung-Geol; Rhim, Hyewhon; Cho, Ssang-Goo (Frontiers in Cell and Developmental Biology, 2020)
Autophagy, a cellular self-digestion process that is activated in response to stress, has a functional role in tumor formation and progression. Cancer stem cells (CSCs) accounting for a minor proportion of total cancer cells-have distinct self-renewal and differentiation abilities and promote metastasis. Researchers have shown that a numeral number of natural products using traditional experimental methods have been revealed to target CSCs. However, the specific role of autophagy with respect to CSCs and tumorigenesis using natural products are still unknown. Currently, CSCs are considered to be one of the causative reasons underlying the failure of anticancer treatment as a result of tumor recurrence, metastasis, and chemo- or radio- resistance. Autophagy may play a dual role in CSC-related resistance to anticancer treatment; it is responsible for cell fate determination and the targeted degradation of transcription factors via growth arrest. It has been established that autophagy promotes drug resistance, dormancy, and stemness and maintenance of CSCs. Surprisingly, numerous studies have also suggested that autophagy can facilitate the loss of stemness in CSCs. Here, we review current progress in research related to the multifaceted connections between autophagy modulation and CSCs control using natural products. Overall, we emphasize the importance of understanding the role of autophagy in the maintenance of different CSCs and implications of this connection for the development of new strategies for cancer treatment targeting natural products.